Fungal communities in European alpine soils are not affected by short‐term in situ simulated warming than bacterial communities. (12th June 2022) - Sannino, Ciro; Cannone, Nicoletta; D'Alò, Federica; Franzetti, Andrea; Gandolfi, Isabella; Pittino, Francesca; Turchetti, Benedetta; Mezzasoma, Ambra; Zucconi, Laura; Buzzini, Pietro; Guglielmin, Mauro; Onofri, Silvano
Abstract: The impact of global warming on biological communities colonizing European alpine ecosystems was recently studied. Hexagonal open top chambers (OTCs) were used for simulating a short‐term in situ warming (estimated around 1°C) in some alpine soils to predict the impact of ongoing climate change on resident microbial communities. Total microbial DNA was extracted from soils collected either inside or outside the OTCs over 3 years of study. Bacterial and fungal rRNA copies were quantified by qPCR. Metabarcoding sequencing of taxonomy target genes was performed (Illumina MiSeq) and processed by bioinformatic tools. Alpha‐ and beta‐diversity were used to evaluate the structure of bacterial and fungal communities. qPCR suggests that, although fluctuations have been observed between soils collected either inside and outside the OTCs, the simulated warming induced a significant ( p < 0.05) shift only for bacterial abundance. Likewise, significant ( p < 0.05) changes in bacterial community structure were detected in soils collected inside the OTCs, with a clear increase of oligotrophic taxa. On the contrary, fungal diversity of soils collected either inside and outside the OTCs did not exhibit significant ( p < 0.05) differences, suggesting that the temperature increase in OTCs compared to ambient conditions was not sufficient to change fungal communities.